Effect of Time Stepping in the Filtering Process on the Synthesis of Nickel Sulfate Powder from Blast Furnace Ferronickel - Fulesa, Aprilio Muhammad; Setiyorini, Yuli; Abdul, Fakhreza; Pintowantoro, Sungging (Applied Science and Engineering Progress, 2024)
The demand for nickel manganese cobalt (NMC)-type batteries is increasing along with the need for global electric vehicles, such as electric cars. Nickel used in the manufacture of NMC batteries is Nickel (II) sulfate hexahydrate (NiSO4.6H2O). Therefore, it is necessary to study how to synthesize nickel sulfate powder from blast furnace ferronickel to provide an alternative source of nickel sulfate and increase the added value of blast furnace ferronickel products. This study aims to analyze the effect of variations in the time difference of stepped filtering sludge on the precipitated filtrate. This study uses a nickel source from the ferronickel derived from the sintering and smelting process using a Mini Blast Furnace to synthesize nickel sulfate. First, the ferronickel was ground and sieved to pass 50 mesh size. Then, the leaching process was performed using a mixture of 120 mL H2SO4 (2M) and 30 mL H2O2 (30%) with a stirring speed of 200 rpm for 6 h for each 2 g ferronickel. Next, the precipitation process was carried out using CaCO3 powder to pH 3.01 at 90 °C. The precipitation solution was held at 90 °C for 24 h, and stepped filtering of the precipitate formed with variations of 2, 4, 6, and 8 h (the total time is kept the same, i.e., 24 h). The crystallization results were then washed and dried at 70 °C for 2 h. Based on X-Ray Fluorescence (XRF), the best results were obtained in stepped filtering variation every 8 h with 50.23% Ni content and 90.5% Ni separation efficiency. Based on XRD, the nickel sulfate powder product has the compound NiSO4.6H2O. In addition, nickel sulfate products also contain CoSO4, one of the compounds needed to manufacture NMC batteries. However, nickel sulfate powder products still contain impurity compounds like FeSO4 and CaSO4.